Moulin Rouge! [compact disc]. - Bowie, David; Aguilera, Christina, 1980-; Lil' Kim; Mýa, 1979-; Fatboy Slim, 1963-; McGregor, Ewan, 1971-; Beck; Wainwright, Rufus, 1973-; Bono, 1960-; Kidman, Nicole, 1967-; Valerii͡a (Singer); Luhrmann, Baz (Interscope Records, 2001)
The soundtrack to Moulin Rouge bounces back and forth between hip tracks from big artists to big Broadway-style ballads from the cast of the film with some of the most well respected names in music such as the popular Lady Marmalade.